IMPLEMENTASI STOIKISME SENECA SEBAGAI SOLUSI FILOSOFIS DALAM MENGHADAPI QUARTER LIFE CRISIS (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Quarter-life crisis is a critical phase commonly experienced by individuals in early adulthood,marked by confusion about life direction, pressure of expectations, and anxiety about the future.In the digital era, social media exacerbates this crisis through mechanisms of unhealthy socialcomparison and unrealistic life expectations. Psychological symptoms such as anxiety, FOMO,and impostor syndrome have become increasingly prevalent. In such conditions, philosophicalreflection becomes essential as a form of existential recovery. Stoic philosophy, particularlythe thoughts of Seneca, offers a practical approach through principles such as the dichotomyof control, negative visualization, and journaling, which help individuals reorganize theirvalues and sense of direction. This study employs a qualitative approach based on literaturereview to examine the interrelation between the quarter-life crisis, the influence of social media,and the relevance of Stoicism. The findings indicate that Stoicism is not merely an ancientphilosophical heritage, but a contextual and applicable guide for the modern generation. Itsphilosophical values contribute to building mental resilience, inner tranquility, and wisdom infacing life’s pressures. Thus, this article asserts that philosophy can serve as a meaningfulspace of recovery for those seeking direction amidst the turbulence of contemporary life.
Keywords: quarter-life crisis, social media, stoicism, seneca, philosophy of life